Influence of Deposition Parameter to Wear Behaviour of Tungsten Carbide-Nickel (WC-Ni) High Velocity Oxyfuel (HVOF) Coating - Abdul Patar, Mohd Affifudin; Kamdi, Z. (Journal of Science and Technology, 2018)
This study is done to investigate the influence of deposition parameter to the hardness and wear resistance of the tungsten carbide nickel (WC-Ni) High velocity oxy-fuel (HVOF) coating which is sprayed on the AISI 1040 medium carbon steel. Three different spraying parameters were used with the oxygen flowrate of each being changed and all other parameters and its value is kept constant. Oxygen flowrate of 30, 45 and 60 LPM were used. The result of hardness, wear rate and surface morphology were compared between the coatings. To compare the surface morphology of the three different parameter HVOF coatings, a scanning electron microscope was used. No significant changes shown on the surface of the coatings where all shows the same lump and crevices structure. X-ray diffraction was used to observe the elemental composition on the three coatings, all the coatings have the same elements present on them. It can be seen that all the coatings contains nickel, tungsten carbide, tungsten (II) carbide and oxygen. The method used for hardness test was the Vickers microhardness tester while weight loss test was used to study the wear resistance. Following the test, it is found that the hardness and wear resistance increased as the oxygen flowrate was increased. The highest hardness and wear resistance can be found in the coating with 60 LPM oxygen flowrate.